The clinical role of LASER for vulvar and vaginal treatments in gynecology and female urology: An ICS/ISSVD best practice consensus document - TARCAN, TUFAN (WILEY, 2019)
BACKGROUND The clinical role of LASER for vulvar and vaginal treatments in gynecology and female urology is controversial. AIMS In this best practice document, we propose recommendations for the use of LASER for gynecologic and urologic conditions such as vulvovaginal atrophy, urinary incontinence, vulvodynia, and lichen sclerosus based on a thorough literature review. MATERIALS & METHODS This project was developed between January and September 2018. The development of this document followed the ICS White Paper Standard Operating Procedures. RESULTS Most of the available studies are limited by their design; for example they lack a control group, patients are not randomized, follow up is short term, series are small, LASER is not compared with standard treatments, and studies are industry sponsored. Due to these limitations, the level of evidence for the use of LASER in the treatment of these conditions remains low and does not allow for definitive recommendations for its use in routine clinical practice. Histological evidence is commonly reported as proof of tissue regeneration following LASER treatment. However, the histological changes noted can also be consistent with reparative changes after a thermal injury rather than necessarily representing regeneration or restoration of function. The use of LASER in women with vulvodynia or lichen sclerosus should not be recommended in routine clinical practice. There is no biological plausibility or safety data on its use on this population of women. DISCUSSION The available clinical studies do not present convincing data regarding the efficacy of LASER for the treatment of vaginal atrophy or urinary incontinence. Also, while short-term complications seem to be uncommon, data concerning long-term outcomes are lacking. CONCLUSION At this point, LASER is not recommended for routine treatment of the aforementioned conditions unless part of well-designed clinical trials or with special arrangements for clinical governance, consent, and audit.
Keywords: genitourinary syndrome of menopause; ICS; ISSVD; LASER; lichen sclerosus; urinary incontinence; vulvovaginal atrophy; vaginal laxity; STRESS URINARY-INCONTINENCE; FRACTIONAL MICROABLATIVE CO2-LASER; ERBIUM-YAG LASER; QUALITY-OF-LIFE; GENITOURINARY SYNDROME; LICHEN-SCLEROSUS; BREAST-CANCER; RADIOFREQUENCY TREATMENT; SEXUAL FUNCTION; 2ND-GENERATION THERMOTHERAPY